A study on the terrestrial mobility of a spherical amphibian robot - Bahar, Mohd Bazli; Abdullah, Shahrum Shah; Mohd Aras, Mohd Shahrieel; Harun, Mohamad Haniff; Aripin, Muhamad Khairi; Ali @ Ibrahim, Fariz (International Islamic University Malaysia, 2024)
Amphibian spherical robots are an appealing and practical alternative that can move around on different surfaces and function in aquatic environments. Spherical robots boast remarkable mobility and robustness, enabling them to navigate and perform exploration and reconnaissance tasks even in challenging or harsh environments. This paper explores assessing the terrestrial travel capabilities of a proposed amphibian spherical robot. A rapid Prototyping machine (RPM) was used to print the prototype’s main shell, yoke, and circuit holders. One main circuit was built on the yoke, while the other was positioned in th e b ottom shell. The driving principle used the barycentre offset notion, in which a pendulum mass isused to vary the location of the mass to generate a motion. Additional mass is added to the pendulum to d etermin e th e robot’s performance when mass is altered. The results reveal that the robot can travel on land with a maximum velocity of 40.75 degrees per second while carrying 600 grams of weight and a turning angle of 22.8 degrees. The robot can only move when the additional mass exceeds 400 grams.